Vagus nerve stimulation as a potential treatment for acute asthmatic bronchoconstriction: a systematic review - Di Flumeri, Elizabeth; Ducharme, Francine M.; St-Pierre, Joël; Niazi, Farbod; Shlobin, Nathan A.; Couillard, Simon; Praud, Jean-Paul; Weil, Alexander G.; Iorio-Morin, Christian (Frontiers in Physiology, 2025)
ObjectiveVagus nerve stimulation (VNS) is a therapeutic option for diseases such as epilepsy and depression. Given that the smooth muscle of the bronchi is innervated by the vagus nerve, VNS could aid in treating pathologies of the respiratory system involving a bronchoconstrictive component. The aim of this review is to evaluate the literature on the potential for VNS to relieve airway bronchoconstriction in asthma.MethodsA systematic review of several databases (PubMed, Embase and Scopus) was conducted according to the PRISMA guidelines. Studies of individuals (humans and animals) with asthma symptoms were included if they reported respiratory function outcomes. Two authors independently reviewed all papers for selection, methodological assessment, and data extraction.ResultsA total of 2072 articles were identified, of which 1,528 unique articles were screened for inclusion. 30 relevant articles underwent full-text review, and six articles (four in humans; two in animals) were included. One human article was subsequently added manually due to a new finding in an updated search. Due to incomplete data reporting, meta-analysis was not possible. In both animal studies, low-voltage VNS improved respiratory function following a histamine or acetylcholine challenge. In human studies (one case report, two prospective interventional cohort studies, one randomized controlled study), VNS, in addition to standard-of-care anti-asthmatic therapy, appears to temporarily improve respiratory function.ConclusionLimited low-quality evidence suggests low-voltage VNS appears to reduce bronchoconstriction in both animal and human subjects. Given concerns about translatability, the absence of a control group in most studies, and the concomitant use of anti-asthmatic pharmacotherapy, it is not possible to draw conclusions about the true magnitude of VNS’s effect on respiratory function and acute asthma progression. Well-designed randomized controlled trials (RCT) are needed to further evaluate the effectiveness of VNS in treating acute asthmatic bronchoconstriction and to better understand its underlying therapeutic mechanisms.